If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6.3 = (x * 9.36) + (y * 5.04) Reorder the terms for easier multiplication: 6.3 = (9.36x) + (y * 5.04) Reorder the terms for easier multiplication: 6.3 = (9.36x) + (5.04y) Solving 6.3 = (9.36x) + (5.04y) Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '(-9.36x)' to each side of the equation. 6.3 + (-9.36x) = (9.36x) + (-9.36x) + (5.04y) Combine like terms: (9.36x) + (-9.36x) = 0.00 6.3 + (-9.36x) = 0.00 + (5.04y) 6.3 + (-9.36x) = (5.04y) Add '-6.3' to each side of the equation. 6.3 + -6.3 + (-9.36x) = -6.3 + (5.04y) Combine like terms: 6.3 + -6.3 = 0.0 0.0 + (-9.36x) = -6.3 + (5.04y) (-9.36x) = -6.3 + (5.04y) Divide each side by '-9.36'. x = 0.6730769231 + (-0.5384615385y) Simplifying x = 0.6730769231 + (-0.5384615385y)
| 6.3=(6.3-x*5.04)+(x*5.04) | | 6x+10=-95-9xs | | 56x-2=6+2x | | 4y+3=-2 | | m+5=-3 | | 3x(x^2+6x)= | | 19=5a+126b | | 2m+5=3m-7 | | 19=5a+12b | | x+4=2y-10 | | Cosx=.23 | | 4+x=5x-9-(2x-3) | | 0.6x+0.8=0.28x+1.16 | | 2x+21=16-3x | | (4x-3)-5=7 | | (x^4)-(2x^2)-1=0 | | (x+2)+(y-5)=8 | | Xlog=4 | | 5x+2y=2x-4y | | (4x)*(4x)+(x+1)*(x+1)=(5x-1)*(5x-1) | | 5x+12=30-9x | | 5x^6-16x^4-x^3-5=0 | | cotx+2=0 | | 4x+(x+1)=5x-1 | | 5x-20=3-8 | | A/H=B/ | | x-(x-3)+(2x+1)=14 | | 5ln(x+1)=x | | T^3=0.125 | | 12x-5=8x+13 | | 5-(3x+2.5)=1 | | x^2+x=183 |